1994
DOI: 10.1159/000126639
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pituitary Prolactin and Adrenocortical Response to Ether, Formalin or Restraint in Lactating Rats: Rise in Corticosterone, but No Increase in Plasma Prolactin Levels after Exposure to Stress

Abstract: It is well established that stress causes a rise in plasma prolactin (PRL) levels of male or cycling female rats. In lactating animals, the pituitary PRL response to stress is not well understood. Therefore, the purpose of the present study was to analyze this question in lactating rats having low or elevated prestress plasma PRL levels. The animals were exposed to ether, formalin or restraint, and plasma PRL and corticosterone levels were determined. In mothers continually together with their pups, plasma PRL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
28
0
2

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 22 publications
2
28
0
2
Order By: Relevance
“…Interestingly, a gradual decrease in plasma PRL levels after stress has also been observed in the lactating rat (12,16) and in lactating women (17), whereas PRL levels increased in nonlactating animals and humans. In light of these findings, it may be speculated that the prolonged decrease observed in the present study might not only be due to the cessation of suckling, but could also represent a specific response to the mental stressor.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Interestingly, a gradual decrease in plasma PRL levels after stress has also been observed in the lactating rat (12,16) and in lactating women (17), whereas PRL levels increased in nonlactating animals and humans. In light of these findings, it may be speculated that the prolonged decrease observed in the present study might not only be due to the cessation of suckling, but could also represent a specific response to the mental stressor.…”
Section: Discussionmentioning
confidence: 83%
“…Observations in the lactating rat have shown an endocrine hyporesponsiveness to physical and psychological stressors, including attenuated secretion of ACTH (3)(4)(5)(6)(7), corticosterone (3-5, 8 -11), catecholamines (12), oxytocin (9,(13)(14)(15), and PRL (12,16).…”
mentioning
confidence: 99%
“…Banky et al reported that domperidone administration markedly decreased prolactin levels in animals subjected to restraint stress. 32) The plasma ACTH-IS level-time profile when blood was sampled at intervals of 120 min is shown in Fig. 3a (dotted line).…”
Section: Resultsmentioning
confidence: 99%
“…What is not well known is that under certain conditions stress can also induce a decrease in PRL secretion. The conditions whereby stress has no effect or even decreases plasma PRL are those where PRL secretion is elevated such as in lactating rats or during the proestrous afternoon surge and during the nocturnal surge of pseudopregnancy [15, 16]. …”
Section: Introductionmentioning
confidence: 99%